USING SOME ENTOMOPATHOGENIC FUNGI TO CONTROL THE RED RUST BEETLE Tribolium castaneum (Hbst.) (Coleoptera : Tenebrionidae). - Mutnai, Hussein Ali; Kamass, Nihad Aziz; Sultan, Ammar Ahmad; Al Saidy, Hadi Alwan (Diyala Agricultural Sciences Journal, 2013)
A study was conducted in the laboratory of microbiology –College of Agriculture - University of Diyala. Form March until June 2013 - to compare the effect of some Entomo pathogenic Fungi in to control on the rust red beetle (Tribolium castaneum) and different concentrations, and the results showed outweigh the treatment of pathogenic fungus Beauveria bassiana isolation local BSA3 significantly (P <0.05) by the second concentrations (35 × ) spore / ml) in recording the highest rates of death in star larvae first insect beetle 52.5%, did not differ with treatments fungus (isolation BSA3) first (57 × ) spore / ml) and the product's commercial pathogen fungus Lecanicillium muscarium (Mycotal) concentrations1 × spore / ml significantly rates of death 42.0% and 46.5%, respectively, while given treatment fruit body extract of the fungus pathogen Calvatia carniiforms lower rates of death for the larvae of a red beetle rusteisect 21.5%, which differed significantly from the treatment comparison 8.5%. And given the fungus treatment B. bassiana isolation BSA3 (second concentrations 35 × ) spore / ml) and the treatment of the preparation commercial Mycotal of the fungus L. muscarium concentrations 1 × spore / ml higher rates of loss in adults insect 41.5% and 38.5% respectively, while recent treatment did not differ significantly from the treatment of fungus B. bassiana (first concentrations), amounting to 35%. Treatment showed fungus B. bassiana isolation BSA3( second concentrations 35× spore/ml) Significant differences in the percentage of adult emergence of a red beetle rusteinsect when the treatment of insect pupae 77.5% .